Electrospun Silicon Nanoparticle/Porous Carbon Hybrid Nanofibers for Lithium‐Ion Batteries. Issue 16 (6th March 2013) - Zhou, Xiaosi; Wan, Li‐Jun; Guo, Yu‐Guo
<x xml:space="preserve">Abstract</x> Si–C hybrid nanofibers with a core‐shell structure of Si nanoparticles confined in porous carbon nanofibers are fabricated by a single‐nozzle electrospinning technique. The as‐obtained Si nanoparticles/porous carbon hybrid nanofibers exhibit excellent properties in terms of cycling performance and rate capabilities for application as anode materials for lithium‐ion batteries. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>